(untitled) (Bodhi Path, 2021)
This research paper explores the relationship between Tibetan Buddhism and commodification. It outlines the way Tibetan Buddhists are economically engaged in society and the way Buddhist’s tangible and intangible objects are being commodified by the refugee Buddhist community in Dharamshala, Himachal Pradesh. Buddhism is often projected by western thinkers and authors as a religion that is based on non- materialism. Lord Buddha rejected his luxurious life and later attained liberation. He gave teachings to his followers about the way a person should engagement with economic practices. Lord Buddha was a firm believer that a person with economic sustenance should become a monk.